Data for: It’s complicated: Maillard, umami and flavor complexity are not key factors in liking of plant-based burgers in a real consumption context - Baptista, Iuri; Harcevic, Agnes; Westling, Magnus; Öström, Åsa (Örebro University, 2026)
Raw data from two field studies with 612 paying customers at a restaurant in Örebro, Sweden. In the first study, a control gray pea burger was compared to an umami burger (with added monosodium glutamate), a Maillard burger (grilled) and a complexity burger (MSG and grilled). In the second study, a simplified control gray pea burger was compared to an enhanced complexity burger (MSG, aromatics, and grilled). Participants were asked for their gender, age group, if they were student, how frequently they ate lunch at the restaurant, what would make them eat more often at the restaurant, what did they think of the potatoes wedges, what did they think of the burger, would they buy that meal if it was offered in the menu, and how would they describe the burger, Answers were collected using EyeQuestion in May of 2025.

Rådata från två fältstudier med 612 betalande kunder på en restaurang i Örebro, Sverige. I den första studien jämfördes en kontrollhamburgare med grå ärtor med en umamiburgare (med tillsatt mononatriumglutamat), en Maillard-burgare (grillad) och en komplexitetsburgare (MSG och grillad). I den andra studien jämfördes en förenklad kontrollhamburgare med grå ärtor med en burgare med ökad komplexitet (MSG, aromatiska ingredienser och grillad). Deltagarna tillfrågades om kön, åldersgrupp, om de var studenter, hur ofta de åt lunch på restaurangen, vad som skulle få dem att äta oftare på restaurangen, vad de tyckte om potatisklyftorna, vad de tyckte om burgaren, skulle de köpa den måltiden om den erbjöds på menyn och hur de skulle beskriva burgaren. Svaren samlades in med hjälp av EyeQuestion i maj 2025.
Data for: It’s complicated: Maillard, umami and flavor complexity are not key factors in liking of plant-based burgers in a real consumption context
Keywords: sensory evaluation; sensorisk bedömning; vegetarian dishes; vegetariska rätter; restaurant sector (lines of business); restaurangbranschen; umami; umami; food recipes; matrecept; ecological sustainability; ekologisk hållbarhet; food services; matservice; Maillard reaction; Maillard-reaktion; Culinary Arts; Kulinariska konster; Interdisciplinary Studies in Humanities and Arts; Tvärdisciplinära studier i humaniora och konst